An Integrative Method for Active Learning: Convergencia 3.0 - Leiva-Lobos, E (IEEE Computer Society, 2020)
This article presents Convergence 3.0, a comprehensive method for the design of active learning environments in distance education. It is based on a class of generative learning objects coined by the name boki. It was implemented using the new functionalities offered by Google Sites in a blended learning context. Convergence 3.0 uses the TPACK framework to design learning environments that brings together pedagogical, technological, and content aspects. Specifically, a connectionist learning style is adopted by applying various active learning techniques used in education 3.0 the versatility of the artifact is shown by presenting it as a design pattern adaptable to different contexts in distance education. To illustrate this characteristic, Convergence 3.0 was used to implement a final year course in a computing engineering degree. Finally, some reflections are made based on the experience achieved in recent years using this method, such as the democratization of the classroom and continuous improvement. © 2020 IEEE.